2012
DOI: 10.1212/wnl.0b013e318247cc7a
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized trial of varenicline (Chantix) for the treatment of spinocerebellar ataxia type 3

Abstract: This study provides Class II evidence that varenicline improved the axial functions of gait, stance, and timed 25-foot walk but did not improve appendicular function, except for rapid alternating movements, in adult patients with genetically confirmed SCA3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 9 publications
4
75
0
5
Order By: Relevance
“…However, there were no issues with vomiting in our studies when varenicline treatment was initiated at a low dose and incrementally increased in half-log intervals, suggesting it may be useful for the treatment of LIDs. Notably, a recent clinical trial showed that varenicline also improved gait and stance in patients with spinocerebellar ataxia and was fairly well tolerated (Zesiewicz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no issues with vomiting in our studies when varenicline treatment was initiated at a low dose and incrementally increased in half-log intervals, suggesting it may be useful for the treatment of LIDs. Notably, a recent clinical trial showed that varenicline also improved gait and stance in patients with spinocerebellar ataxia and was fairly well tolerated (Zesiewicz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are ongoing studies with stem cell therapy for other SCAs [NCT01489267, NCT01958177]; however these studies are open labeled, which will limit the conclusions regarding efficacy of this therapy. 9.4 Clinical trials and other studies for symptomatic treatments 9.4.1 Ataxia 9.4.1.1 Varenicline Efficacy of the partial agonist of a4b2 nicotinic acetylcholine receptors varenicline on ataxia was evaluated during 8 weeks in 20 SCA3/MJD patients in a double-blind, placebocontrolled RCT [92]. Nine individuals were analyzed per group and the results were contradictory in an exploratory analysis of SARA (e.g., improvement in the item gait and worsening in the item stance).…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Varios estudios recientes indican que la vareniclina, un agonista parcial del receptor nicotínico α4β2, mejora los síntomas de pacientes con ataxia neurodegenerativa de distintas etiologías 2,3 . Los mecanismos de acción propuestos en base a estudios animales son múltiples: incremento de sobrevida y conectividad de neuronas olivocerebelosas; reducción de las disquinesias producidas por L-dopa; liberación de dopamina a nivel presináptico; incremento de la activación funcional del vermis cerebeloso e incremento del flujo cerebral del circuito tálamo-cortical y protección contra la muerte de neuronas motoras en cultivos de medula espinal 2,3 .…”
unclassified
“…Los mecanismos de acción propuestos en base a estudios animales son múltiples: incremento de sobrevida y conectividad de neuronas olivocerebelosas; reducción de las disquinesias producidas por L-dopa; liberación de dopamina a nivel presináptico; incremento de la activación funcional del vermis cerebeloso e incremento del flujo cerebral del circuito tálamo-cortical y protección contra la muerte de neuronas motoras en cultivos de medula espinal 2,3 . Todo ello sería por la presencia de múltiples receptores nicotínicos en el cerebelo (ubicados en la células granulares, células de Purkinje e interneuronas), además del resto del cerebro, en orden de concentración decreciente (α4β2 > α3β4 > α3β2β4 > α3α4β2) 2,3 . Los efectos clínicos de los agonistas nicotínicos fueron reproducidos en modelos animales de ataxia olivocerebelosa 3 .…”
unclassified
See 1 more Smart Citation